Pemanfataan Media Dalam Memahami Realitas Sosial Di Kalangan Mahasiswa UIN SGD Bandung - dulkiah, moh (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2013)
This article explores social fenomena using mass media among students of UIN Sunan Gunung Djati, Bandung. The Aim of using mass media is to reduce the gap of information between theory and social phenomena. The study finds that the users of mass media among the studentsare divided into four clusters:the reader (using printing media), the watcher (using electronic media), the observer (using less all media), and the anti-observer (not using all media),the finding of which describing that many students focused more on observerclusters.